2017
DOI: 10.2134/ael2017.02.0004
|View full text |Cite
|
Sign up to set email alerts
|

Linking Soil Phosphorus to Dissolved Phosphorus Losses in the Midwest

Abstract: Core Ideas Soil test phosphorus remains an important factor in studying dissolved reactive P loss. Identifying higher risk fields with STP could inform future management practices to reduce DRP loss. STP was linearly related to DRP concentration loads in tile‐drained fields. Monitoring STP in addition to implementing other BMPs should be considered to decrease DRP loss. Harmful and nuisance algal blooms resulting from excess phosphorus (P) have placed agriculture in the spotlight of the water quality debate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 32 publications
4
62
0
Order By: Relevance
“…Therefore, this study further highlights the urgent need identified by Duncan et al. (2017) to reanalyze the agronomic recommendations where the buildup or maintenance approach to fertilizer applications may turn soils into P sources, exacerbating DRP losses to surface waters.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Therefore, this study further highlights the urgent need identified by Duncan et al. (2017) to reanalyze the agronomic recommendations where the buildup or maintenance approach to fertilizer applications may turn soils into P sources, exacerbating DRP losses to surface waters.…”
Section: Resultsmentioning
confidence: 63%
“…Duncan et al. (2017) found that Ohio soils with STP values above the regionally recommended agronomic critical STP (Vitosh et al., 1995) were more likely to lose DRP at annual concentrations above the 0.05‐mg P L −1 USEPA‐mandated threshold (USEPA, 2017). Therefore, this study further highlights the urgent need identified by Duncan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Legislation to help reduce STP levels to the agronomic optimum has been generally slow to implement despite widespread eutrophication problems, and there is a lack of general guidelines on ways to manage a reduction in STP and the amount by which to reduce it. Even if soil P concentrations were reduced to the agronomic optimum, it is not clear whether this is sufficient to reduce P concentrations in runoff sufficiently to help alleviate eutrophication problems (Cassidy et al, 2017; Duncan et al, 2017). The concentrations of SRP or total P required to limit algal growth in flowing and standing waters are extremely low (20–100 μg L −1 ) in relation to the variably high concentrations of P (often >1–2 mg L −1 ) in runoff from agricultural soils (Chambers et al, 2012; Withers and Bowes, 2018).…”
mentioning
confidence: 99%
“…When phosphorus inputs into the watershed are greater than deliberate phosphorus outputs, either ∆P or the soil test phosphorus (STP) concentrations within the watershed increase or phosphorus is running off the landscape and into the watershed's waterways. Research has demonstrated decreased dissolved phosphorus runoff losses as STP concentrations decline (Duncan et al, 2017). When this is not the case, it could mean that the fertilizer or manure applied was lost to surface runoff before crop utilization.…”
Section: Agricultural System Phosphorus Balance and Use Efficiencymentioning
confidence: 99%